How do physicists use an e-print archive? Implications for institutional e-print services - Pinfield, Stephen (2001)
It has been suggested that institutional e-print services will become an important way of achieving the wide availability of e-prints across a broad range of subject disciplines, but as yet there are few exemplars of this sort of service. This paper describes how physicists make use of a successful subject-based e-prints service, arXiv (formerly known as the Los Alamos XXX service), and discusses the possible implications of this for institutional multidisciplinary e-print archives. A number of key points are identified, including technical issues (such as file formats and user interface design), management issues (such as submission procedures and administrative staff support), economic issues (such as installation and support costs), quality issues (such as peer review and quality control criteria), policy issues (such as digital preservation and collection development standards), academic issues (such as scholarly communication cultures and publishing trends), and legal issues (such as copyright and intellectual property rights). These are discussed with reference to the project to set up a pilot institutional e-print service at the University of Nottingham. This project is being used as a pragmatic way of investigating the issues surrounding institutional e-print services, particularly in seeing how flexible the e-prints model actually is and how easily it can adapt itself to disciplines other than physics.